The art and ‘science’ of opera: composing, staging & designing new forms of interactive theatrical performance - Chamberlain, Alan; Kallionpää, Maria; Benford, Steve (2017)
New technologies, such as Virtual Reality (VR), Robotics and Artificial Intelligence (AI) are steadily having an impact upon the world of opera. The evolving use of performance-based software such as Ableton Live and Max/MSP has created new and exciting compositional techniques that intertwine theatrical and musical performance. This poster presents some initial work on the development of an opera using such technologies that is being composed by Kallionpää and Chamberlain.